1999
DOI: 10.1097/00007890-199903150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Living Kidney Donors: Quality of Life After Donation1

Abstract: The University of Minnesota has been a strong advocate of living donor kidney transplants. The benefits for living donor recipients have been well documented. The relative low risk of physical complications during donation has also been well documented. Less well understood is the psychosocial risk to donors. Most published reports have indicated an improved sense of well-being and a boost in self-esteem for living kidney donors. However, there have been some reports of depression and disrupted family relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
239
2
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(274 citation statements)
references
References 12 publications
26
239
2
7
Order By: Relevance
“…Первые работы, посвященные КЖ при-жизненного органного донора, проводились в конце 1990-х годов и были посвящены донорам почки. Ре-зультаты исследований показали высокие парамет-ры КЖ прижизненных доноров в послеоперацион-ном периоде [35,36].…”
Section: исследования кж прижизненного органного донораunclassified
“…Первые работы, посвященные КЖ при-жизненного органного донора, проводились в конце 1990-х годов и были посвящены донорам почки. Ре-зультаты исследований показали высокие парамет-ры КЖ прижизненных доноров в послеоперацион-ном периоде [35,36].…”
Section: исследования кж прижизненного органного донораunclassified
“…2,3,10,15 Studies have also consistently found that a small proportion of donors (<10%) regretted their decision to donate or would not donate again. 2,3,9,11,12 The proportion of donors who felt pressure to donate their kidney varied across studies. The major concerns of donors related to postoperative pain (with some donors reporting the surgery as the most painful experience ever encountered), length of recovery, recipient wellbeing, health, employment issues, financial problems, health risks and lifestyle restrictions.…”
Section: What Is the Evidence?mentioning
confidence: 99%
“…1 Live donors are not only at risk of physical adverse events including infection and loss of renal function in the remaining kidney but they may also experience psychosocial problems including anxiety, depression, regret and financial hardship. 2,3 The psychosocial evaluation of donors (pre-and posttransplant) is widely advocated; 4 however, there is a paucity of data on the process and content of psychosocial evaluations. For example, there are no set standards regarding who should conduct psychosocial evaluations (physician, psychiatrist, psychologist, medical social worker), whether evaluations should be mandatory, at what stage of the work-up evaluations should be conducted, at what time interval repeat evaluations should be performed and what criteria need to be met.…”
Section: Introductionmentioning
confidence: 99%
“…20 Still, the vast majority of donors understand this risk and do not regret their decision. [21][22][23] Another risk is the potential coercive nature of the request: how can children refuse when their parents are asking them to donate? 16,17 And, if a child does refuse, additional guilt may result.…”
Section: Risk/benefit Ratiomentioning
confidence: 99%
“…[52][53][54] The minor needs to understand that the donated organ may fail or may be rejected by the recipient or that the original cause of the organ failure may recur and that the outcome is beyond his or her control. 19,21,53 The literature shows that many donors feel neglected after donation as the focus returns to the ill recipient. 52,55 Family members should be reminded that they need to be attentive to the needs of both the donor and the recipient.…”
Section: Informed Consentmentioning
confidence: 99%